2017
DOI: 10.3389/fcimb.2017.00224
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Differences in Virulence Markers Associated with Achromobacter Species of CF and Non-CF Origin

Abstract: Achromobacter spp. are recognized as emerging pathogens in hospitalized as well as in cystic fibrosis (CF) patients. From 2012 to 2015, we collected 69 clinical isolates (41 patient) of Achromobacter spp. from 13 patients with CF (CF isolates, n = 32) and 28 patients receiving care for other health conditions (non-CF isolates, n = 37). Molecular epidemiology and virulence potential of isolates were examined. Antimicrobial susceptibility, motility, ability to form biofilms and binding affinity to mucin, collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
2
28
1
1
Order By: Relevance
“…The most active agents for Achromobacter were SXT and IMI. In contrast to previously published data, MER was less active than IMI [16]. CAZ, COL, and TOB have been considered adequate for inhalation therapy [17]; however, in this study, these antibiotics presented high MIC 90 values.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
See 1 more Smart Citation
“…The most active agents for Achromobacter were SXT and IMI. In contrast to previously published data, MER was less active than IMI [16]. CAZ, COL, and TOB have been considered adequate for inhalation therapy [17]; however, in this study, these antibiotics presented high MIC 90 values.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…Some studies have demonstrated that its presence is associated with a risk of pulmonary exacerbation but not with a worsened long-term prognosis [15]. Also, Achromobacter isolated from people with CF seem to be more virulent than those isolated from other sources [16]. The most active agents for Achromobacter were SXT and IMI.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Achromobacter species are motile due to the presence of flagella, and can exhibit binding factors to mucin, collagen, and fibronectin, thereby facilitating initial attachment and invasion of the respiratory tract. 82,83 Biofilm formation as well as intrinsic resistance to several classes of antimicrobials through the expression of efflux pumps, βlactamases, and aminoglycoside-modifying enzymes [84][85][86] is also expressed by this group of pathogens.…”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 99%
“…The recent review of genetic divergence within the Achromobacter genus resulted in an increase in the number of recorded strains of A. marplatensis , owing to the reclassification of A. spiritinus as A. marplatensis [ 15 , 16 ]. A. marplatensis now carries a newly recognised importance in CF patients, being isolated from more than 10% of patients in a French CF Centre [ 12 ], as well as in CF patients in Argentina [ 17 ], Serbia [ 18 ], Denmark [ 19 ] and the UK [ 20 ].…”
Section: Introductionmentioning
confidence: 99%